Constructions de sémiographies dans les systèmes graphiques de langues régionales - Clara Mortamet (Lengas)
This text presents a later perspective in its author’s work on sociolinguistics of orthography : the writing of vernacular languages. In such a field, she defends the importance of the semiographic components of writing systems to describe and analyse variations of uses and creativity. It allows to focus on social questions, identities, linguistic ideologies, literacy matters as well as linguistics, all particularly relevant in this situation of writing. The articles then examines the situation of the Normand language, from the study of some choices and variations observed in dictionaries, lexicons and phrase books, bringing out some elements of a Normand semiography.